PENGARUH BOKASHI LIMBAH SEKAM PADI TERHADAP PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) - Tenri Sau; Rahmat Zulkifli (UNM Environmental Journals, 2022)
The growth and production of mustard greens requires a growing medium that is fertile, loose, and has good aeration and drainage. Bokashi is an organic fertilizer produced from a fermentation or fermentation process of organic matter, which can increase the availability of nutrients in the planting medium, improve the physical, chemical and biological properties of the soil so that plants can thrive with high production. This experiment was carried out in January-March 2021. The research was located in the Atakkae Village, Tempe District, Wajo Regency. The growth and production of mustard greens requires a growing medium that is fertile, loose, and has good aeration and drainage. Bokashi is an organic fertilizer produced from a fermentation or fermentation process of organic matter, which can increase the availability of nutrients in the planting medium, improve the physical, chemical and biological properties of the soil so that plants can thrive with high production. This experiment was carried out in January-March 2021. The research was located in the Atakkae Village, Tempe District, Wajo Regency. The experiment used a randomized block design with four treatments and three replications, namely: no treatment (control), bokashi 15 kg/bed (50 tons/ha), bokashi 35 kg/bed (116.66 tons/ha), and bokashi 50 kg /bed (166.66 tons/Ha). Each experimental unit consisted of 56 plants which were repeated three times so that there were 672 plants in total. The experimental results on statistical analysis on variance showed that plant height, number of leaves, leaf width, fresh weight of plants, fresh weight per plot had no significant effect, but tended to be best produced by giving bokashi straw 35 kg/bed (116.66 tons/ha)